Use of suggestive seizure manipulation methods in the investigation of patients with possible psychogenic nonepileptic seizures—An international ILAE survey. Issue 3 (31st July 2021) - Gras, Adrien; Wardrope, Alistair; Hirsch, Edouard; Asadi Pooya, Ali A; Duncan, Rod; Gigineishvili, David; Hingray, Coraline; Kanemoto, Kousuke; Ladino, Lady; LaFrance, William Curt; McGonigal, Aileen; Pretorius, Chrisma; et al.
Abstract: Video‐encephalographic (vEEG) seizure recordings make essential contributions to the differentiation of epilepsy and psychogenic nonepileptic seizures (PNES). The yield of vEEG examinations can be increased through suggestive seizure manipulation (SSM) (ie, activation/provocation/cessation procedures), but its use has raised ethical concerns. In preparation for guidelines on the investigation of patients with PNES, the ILAE PNES Task Force carried out an international survey to investigate practices of and opinions about SSM. An online questionnaire was developed by the ILAE PNES Task Force. Questions were asked at clinical unit or individual respondent level. All ILAE chapters were encouraged to send questionnaires to their members. The survey was open from July 1, 2019, to August 31, 2019. A total of 487 clinicians from 411 units across 94 countries responded. Some form of SSM was used in 296/411 units (72.0%). Over 90% reported the use of verbal suggestion, over 80% the use of activation procedures also capable of eliciting epileptic activity (hyperventilation or photic stimulation). Only 26.3% of units used techniques specifically intended to provoke PNES (eg, saline injection). Fewer than 10% of units had established protocols for SSM, only 20% of units required written patient consent, in 12.2% of units patients received explicitly false information to provoke seizures. Clinicians using SSM tended to perceive no ethical problems, whereas those not using SSM were likely to have ethical concerns about these methods. We conclude that the use of invasive nocebo techniques intended to provoke PNES in diagnostic settings has declined, but SSM is commonly combined with activation procedures also capable of eliciting epileptic activity. While research suggests that openness about the use of PNES‐specific nocebo techniques does not reduce diagnostic yield, very few units have suggestion protocols or seek patient consent. This could be addressed through establishing consensus guidance for the practice of SSM.